(untitled) - Nolasco, Rob (Oxford, 1994)
The book aims to develop the written communication of students who are approaching functional competence, at upper-intermediate level. The book concentrates on giving students practice in many aspects of the writing process, including organization, register, style, and tone, through a series of relevant and motivating tasks.
Keywords: English language,English language,English language; Study and teaching,Textbooks for foreign speakers,Writing